1997
DOI: 10.1007/s12122-997-1027-2
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about unions and what they should do: A survey of employed canadians

Abstract: I use IR theory to identify five roles that have been associated with unions in North America and then report the findings from a 1995 survey of employed Canadians, asking them their beliefs about the amount of effort unions place on each of twentyfour activities associated with these roles, the amount of effort unions should place on each, and the amount of success unions have on each. Basically, Canadians want unions to continue to perform their traditional activities, and they view unions as having an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Freeman and Rogers (2006, 1) stated that “even workers whose management had instituted employee involvement committees to consult with them on workplace decisions wanted more voice and power in the process.” However, most workers desired cooperative and nonadversarial relations to reap the full benefits of mutual respect and power sharing (Freeman and Rogers 2006). Godard’s (1997) conclusions from a survey of Canadian workers were similar in that he suggested that unions increase their activities along their integrative function. The integrative function of unions suggests that unions can reduce feelings of discontent, decrease the sense of isolation felt by individual workers, and help build a sense of trust toward management or the organizational status quo through protections, reassurance, and conflict resolution and voice mechanisms.…”
Section: Specific Factors Related To Voting Propensitymentioning
confidence: 88%
“…Freeman and Rogers (2006, 1) stated that “even workers whose management had instituted employee involvement committees to consult with them on workplace decisions wanted more voice and power in the process.” However, most workers desired cooperative and nonadversarial relations to reap the full benefits of mutual respect and power sharing (Freeman and Rogers 2006). Godard’s (1997) conclusions from a survey of Canadian workers were similar in that he suggested that unions increase their activities along their integrative function. The integrative function of unions suggests that unions can reduce feelings of discontent, decrease the sense of isolation felt by individual workers, and help build a sense of trust toward management or the organizational status quo through protections, reassurance, and conflict resolution and voice mechanisms.…”
Section: Specific Factors Related To Voting Propensitymentioning
confidence: 88%
“…These two faces of unionism coincide with the economic equity and workplace democracy objectives of social responsibility. Godard's (1997) survey of Canadian workers resulted in five union roles: (a) economic, maximizing wages and benefits; (b) workplace democratization, securing worker rights and protections; (c) integrative, providing orderly conflict resolution mechanisms; (d) social democratic, addressing broader social issues, and (e) conflict, countervailing the corporate agenda as a general advocate for workers. Godard's economic role is consistent with the economic equity objective and the workplace democratization and integrative functions are subsumed in the workplace democracy objective.…”
Section: Objectives Of Labor Union Social Responsibilitymentioning
confidence: 99%
“…In place of the old theory, which tied propensity to unionize to gender, we see, today, the rise of an analysis which says that gender does not matter-at least, that is the implication when researchers do not reveal the gender composition of their sample (e.g., Wheeler, McClendon and Weikle 1994) or disaggregate their data by gender (e.g., Godard 1997). More common is a finding that women report the same reasons as men for seeking union representation.…”
mentioning
confidence: 99%
“…Yet, they inadvertently underscored the salience of gender as a workplace issue when they reported that clerical workers tended to view unions "as institutions dominated by angry groups of male employees" and that organizing drives directed at women clerical workers must pay "more attention...to building self-confidence." Similarly problematic are the conclusions of Freeman and Rogers (1999), Waddington andWhitston (1997), andGodard (1997). In these studies, participants were asked to respond in a restricted way (e.g., yes/no, a lot/ somewhat/only a little/not at all, and so on) to questions framed by conventional theory and posed at a high level of generality.…”
mentioning
confidence: 99%